2023
DOI: 10.1177/14034948231153913
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of age, gender and occupational group to the higher risk of disability retirement among Finnish public sector employees

Abstract: Background: The aim of this study was to examine the differences in disability retirement between public and private sector employees and to examine the contribution of age, gender and occupational group to the differences between the sectors. Methods: Our Finnish register data consisted of about two million non-retired men and women aged 30–62 years. Cox proportional hazard models were used to calculate hazard ratios for any, full and partial disability retirement in the public sector compared with the privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, the multiple reasons for retirement were not differentiated in the study in order to maintain good statistical precision. The risk of partial disability retirement is lower in the private sector than in the public sector (Polvinen & Laaksonen, 2023).…”
Section: Institutional Context Data and Methodsmentioning
confidence: 99%
“…However, the multiple reasons for retirement were not differentiated in the study in order to maintain good statistical precision. The risk of partial disability retirement is lower in the private sector than in the public sector (Polvinen & Laaksonen, 2023).…”
Section: Institutional Context Data and Methodsmentioning
confidence: 99%
“…Consequently, the risk of partial disability retirement has been shown to be higher in the public sector than in the private sector. 40 Moreover, previous studies have found that partial disability retirement is more common in larger than in smaller workplaces, 41 42 which may indicate that it is easier to provide part-time work in larger working units. This may partly explain the differences in the use of partial disability retirement across sectors, as work units in the public sector are usually larger compared with those in the private sector.…”
Section: Predictors Of Labour Market Paths After Psamentioning
confidence: 99%